Services and library space designed for various learner groups: Case Kaisa House at the University of Helsinki - Weimer, Kristina; Helminen, Päivi (Nordic Journal of Information Literacy in Higher Education, 2013)
In our paper we describe examples of how our new university library supports learning by providing new services in a new building. The examples can be applied in other contexts and in existing libraries. <!–[if gte mso 9]> Normal 0 21 false false false NO-BOK X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>